Inclusion of persons with disability in sport: part 2 – best practices and policy recommendations from Qatar - Josélia Neves (18279010) (2022)
The upcoming FIFA World Cup 2022 has been announced as the most accessible for persons with disabilities (PWDs) in the history of international FIFA tournaments,1 a fact that will have a positive impact on the built environment and the lives of local communities. Such a major sporting event may galvanise the population to undertake greater physical activity, a contribution against obesity and sedentarism in the country. The commitment to a healthier population led to the establishment of National Sports Day, the only public holiday beyond Qatar National Day. It is now acknowledged that all persons have the need and the right to engage in sport, and that PWDs are entitled to adaptations to access sport on equitable terms. Regrettably, there is no centralised data on the participation of PWDs in sport at the national level. The data gathered by different organisations makes comparisons and generalisations impossible. The purpose of this editorial is to offer a brief overview of PWDs’ engagement with sports in Qatar, including CWD, participation in elite parasport, and policy and infrastructure engagement. Other Information Published in: British Journal of Sports Medicine License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1136/bjsports-2022-106225